1994
DOI: 10.1111/j.1399-0004.1994.tb04226.x
|View full text |Cite
|
Sign up to set email alerts
|

Diphallus and associated anomalies with balanced autosomal chromosomal translocation

Abstract: We report a sporadic case of complete diphallus with multiple other anomalies in a premature newborn. Chromosomal analysis at the 500 band level showed an apparently balanced reciprocal translocation 46,XY, t(1;14)(p36.3;q24.3). The mother has a normal karyotype, but the father was not available for chromosomal analysis. The significance of this balanced chromosomal rearrangement and the possibility that the chromosomal breakpoints contribute to deregulation of mesodermal development is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…He had hydrocephaly associated with penoscrotal transposition and oligodactyly, which had never before been reported to be associated in the same patient with this syndrome, although hydrocephalus with or without ambiguous genitalia has been previously reported [Seabright et al, 1979;Chung et al, 2001]. Penoscrotal transposition has been reported as isolated, in association with other malformations or as part of the caudal deficiency sequence [Anlar and Ayabakan, 1986;Lage et al, 1987;Turnock and Brereton, 1991;MacKenzie et al, 1994], as well as in association with a mosaic trisomy 8 karyotype and other chromosomal anomalies, including deletion of 13q [Schofield et al, 1992;Karna and Kapur, 1994;Schinzel, 2001].…”
Section: Discussionmentioning
confidence: 91%
“…He had hydrocephaly associated with penoscrotal transposition and oligodactyly, which had never before been reported to be associated in the same patient with this syndrome, although hydrocephalus with or without ambiguous genitalia has been previously reported [Seabright et al, 1979;Chung et al, 2001]. Penoscrotal transposition has been reported as isolated, in association with other malformations or as part of the caudal deficiency sequence [Anlar and Ayabakan, 1986;Lage et al, 1987;Turnock and Brereton, 1991;MacKenzie et al, 1994], as well as in association with a mosaic trisomy 8 karyotype and other chromosomal anomalies, including deletion of 13q [Schofield et al, 1992;Karna and Kapur, 1994;Schinzel, 2001].…”
Section: Discussionmentioning
confidence: 91%
“…The degree of separation of these cloacal membranes may produce anomalies such as anterior wall defects, bladder exstrophy and hindgut anomalies [7], and may explain the anorectal malformation seen in this case. Karyotype in cases of diphallus has been found to be normal, with the exception of a case described by Karna and Kapur, associated with a balance translocation t(1,14)(p36.3; q24.3) [8]. The latter suggested that defects in homeobox genes, which are thought to be master-controller genes of differentiation, may be involved in diphallus formation and related syndromes.…”
Section: Discussionmentioning
confidence: 88%
“…Homeobox genes, the master controller of differentiation in the development of endoderm and mesoderm of the intestinal tract, may be involved in CDS [5]. The only documented case associated with an abnormal karyotype was reported by Karna and Kapur [5], in a 46, XY male with complete diphallus, and a balance translocation t(1:14)(p36.3;q24.3). No other reports including the current study found any karyotype abnormalities.…”
Section: Discussionmentioning
confidence: 92%